Voices of Difference: A Case Study on the Experiences of International Students at a University in the Southeastern United States - Kelley, Jacob (Journal of Interdisciplinary Studies in Education, 2022)
International students often encounter several challenges during their academic and social journeys at higher education institutions in the United States. The purpose of this case study was to examine the experiences of three international students at a university in the southeastern U.S. The participants were a woman from Colombia, a man from Saudi Arabia, and a woman from China. The researcher used in-depth interviews to collect data for this case study. Findings revealed that participants experienced culture shock, misguided expectations, and a lack of resources. The experiences of the participants suggest that higher education institutions must provide more meaningful and intentional support for international students.